1998
DOI: 10.1021/js970361l
|View full text |Cite
|
Sign up to set email alerts
|

Preparation Characterization Evaluation of Miconazole-Cyclodextrin Complexes for Improved Oral Topical Delivery

Abstract: The solubility of miconazole in water increased in the presence of cyclodextrins (CDs). The apparent K1:1 values calculated from the phase solubility diagrams of gamma-CD, hydroxypropyl-beta-CD, alpha-CD, hydroxyethyl-beta-CD, hydroxypropyl-gamma-CD, and beta-CD were 695 +/- 39.6, 363 +/- 34.1, 333 +/- 18.5, 312 +/- 31.0, 305 +/- 27.6, and 293 +/- 17.6 M(-1), respectively. Solid 1:1 molar complexes were prepared by freeze-drying and kneading and characterized by UV spectroscopy, differential scanning calorimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…The signiˆcant ( p<0.05) decrease in ‰ux value of BCD-colchicine formulation suggests depot-forming ability of formulation. Similarly, Tenjarla et al 28) and Simeoni et al 29) reported reduced skin permeation and increased skin accumulation of miconazole and oxybenzone by cyclodextrin complexation.…”
Section: Resultsmentioning
confidence: 89%
“…The signiˆcant ( p<0.05) decrease in ‰ux value of BCD-colchicine formulation suggests depot-forming ability of formulation. Similarly, Tenjarla et al 28) and Simeoni et al 29) reported reduced skin permeation and increased skin accumulation of miconazole and oxybenzone by cyclodextrin complexation.…”
Section: Resultsmentioning
confidence: 89%
“…The addition of citric acid along with b-cyclodextrin resulted in an increase in solubility of carvedilol to a much greater extent compared to complexation of the drug with b-cyclodextrin alone. This may be attributed to the fact that organic hydroxyl acids such as citric acid are able to enhance the solubility of the basic guest molecule both by forming a salt and by increasing the stability constant of the complex (11). Thus the addition of citric acid results in formation of carvedilol citrate salt (6).…”
Section: Phase Solubility Studiesmentioning
confidence: 99%
“…[14][15][16] These systems have been shown to enhance the antifungal activity of miconazole. 4 To date, 17,18 Solid lipid nanoparticles (SLNs) were developed at the beginning of the 1990s as an alternative particulate delivery system to liposomes, emulsions, microparticles, and polymeric nanoparticulate systems. SLNs combine the advantages of those systems, such as controlled release, biodegradability, biocompatibility, and the protection of the incorporated drug against chemical degradation.…”
Section: Introductionmentioning
confidence: 99%